2019
DOI: 10.1002/anie.201814507
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence Platforms Based on Small Water‐Insoluble Organic Molecules for Ultrasensitive Aqueous‐Phase Detection

Abstract: Highly efficient detection in the aqueous phase for water-insoluble organic molecule probes is challenging.T he bright aggregated-state electrochemiluminescence (ECL) of 1,1-disubstituted 2,3,4,5-tetraphenylsiloles by ac o-reactant approach was discovered, and ah eterogeneous aggregationinduced emission ECL (HAIE-ECL) was constructed at the electrode surface,s howing very high ECL efficiency (37.8 %) and selective recognition for industrially important DNBP plasticizer with al ow detection limit of 0.15 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 65 publications
2
107
0
Order By: Relevance
“…Very recently,t he unique propeller-like structures of 1,1'-disubstituted 2,3,4,5-tetraphenylsiloles (Scheme 1b)h ave been facilely synthesized with simple, non-toxic, and highly stable archetypes of the AIE backbone. [49] The trend of strong AIE effect among these three structures was consistentw ith ECL intensityo rder:D MTPS < MPPS < HPS (Figure 12 a). By contrast, the ECL intensities of these silole monomers in homogeneous organic solvents decreased to approximatelyo ne twentieth (150 vs. 3000, Figure 12 b).…”
Section: Organic Dots (Ods)supporting
confidence: 59%
“…Very recently,t he unique propeller-like structures of 1,1'-disubstituted 2,3,4,5-tetraphenylsiloles (Scheme 1b)h ave been facilely synthesized with simple, non-toxic, and highly stable archetypes of the AIE backbone. [49] The trend of strong AIE effect among these three structures was consistentw ith ECL intensityo rder:D MTPS < MPPS < HPS (Figure 12 a). By contrast, the ECL intensities of these silole monomers in homogeneous organic solvents decreased to approximatelyo ne twentieth (150 vs. 3000, Figure 12 b).…”
Section: Organic Dots (Ods)supporting
confidence: 59%
“…DCM easily dissolves the films of 4T1 and 4T2 and clearly cannot be used. Although aqueous systems are widely reported, the films of 4T1 and 4T2 are highly hydrophobic and show no electrochemical or ECL behavior in purely aqueous system (Figure S3). After screening a number of common solvents for electrochemistry and ECL compatibility, we found that the films have relatively poor solubility in acetonitrile, although they are not yet insoluble enough in acetonitrile (see ECL results in Figure S4).…”
Section: Methodsmentioning
confidence: 54%
“…Highly π‐conjugated compounds containing silole rings (1‐silacyclopentadiene) have been adopted for use in polymeric solar cells, electrochemiluminescent sensors, and light‐emitting diodes . The unique photophysical properties of siloles arise from their low‐lying LUMO due to the σ*‐π* conjugation between the π* orbital of the butadiene moiety and the σ* orbital of the two exocyclic σ‐bonds on the silicon atom.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations